Analysis of the Relationship Between Inflation and Rice Prices in Tulungagung Regency in 2021–2022 - Harisatu Silmina; Runchida Mick Plesri; M. Wahyu Agustino; Agus Eko Sujianto (Cahaya Abadi Publisher, 2026)
This study aims to examine the relationship between inflation and rice prices in Tulungagung Regency during the 2021–2022 period. The data used is secondary data in the form of monthly inflation records and monthly rice prices obtained from official BPS publications. The research approach uses a quantitative method with Pearson correlation analysis to assess the direction of the relationship as well as the strength of the association between the two variables. The results of the analysis showed that the correlation value was 0.746 with a significance level of 0.000 (<0.05). These findings confirm that inflation has a significant and strong positive relationship with rice prices. Thus, an increase in inflation tends to be followed by an increase in rice prices during the study period. This study provides an empirical overview related to food price dynamics and the influence of regional macroeconomic conditions, especially on staple food commodities. The findings are expected to contribute to policy considerations in controlling inflation and maintaining price stability of essential food commodities at the regional level.